ANALYSIS OF COMPONENT 4A IN MANGROVE BOTANICAL GARDEN WONOREJO SURABAYA - Selvi Dwi Fitriani; Joko Mijiarto (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
The Wonorejo Mangrove Botanical Garden is a recommended tourist attraction for tourists exploring nature amidst the hustle and bustle of Surabaya. Although the Wonorejo Mangrove Botanical Garden boasts a rich mangrove ecosystem, diverse flora and fauna, and adequate tourist facilities, improvements are still needed. This study aims to analyze the development of the Wonorejo Mangrove Botanical Garden in Surabaya using the 4A approach, as well as the factors that inhibit and support tourism development. This study was conducted using a descriptive qualitative approach, with data collection through interviews, observation, and documentation. The results indicate that, overall, the development of the Wonorejo Mangrove Botanical Garden can be carried out by optimizing the 4A and mitigating inhibiting factors, thereby improving service quality and competitiveness while balancing economic, environmental, and socio-cultural benefits. This tourist attraction has the potential to be recommended as a natural tourist attraction with a superior ecotourism concept in Surabaya. The development of the Wonorejo Mangrove Botanical Garden in Surabaya is still in the potential stage and not yet optimal. For stakeholders, this can be done by optimizing the 4A components, mitigating the development factors of tourist attractions (both supporting and inhibiting), and adopting a sustainable approach.